# Algebra 1

posted by Annie

simplify

2/x^2-y^2-1/x^2-3xy+2y^2-3/x^2-xy-2y^2

group like terms, and combine them. I see terms 1/x^2, y^2, and xy terms that can be grouped. We will be happy to critique your work.

1. Anonymous

idk what y and x equals

## Similar Questions

1. ### polynomials

(15+11+6x2+1)-(13x2+2) Combine like terms. I will be happy to critique your work on this.
2. ### algebra

3x-5(3x-7)= 2(x+9) + 45 You won't learn unless you try these yourself. Multiply out the term in parentheses, combine the x terms together and the constants together, and then put all the x terms on one side of the = and the constants …
3. ### algerbra help

6x ^2 y^3+9x^2 y^3 __________________ 3x^2 y^2 how do I start to solve this you need to distrubet how do I do that is this right 6x^2 9x^2+y^3xy^3 ?
4. ### math/algebra

add:Express in simplest form 4x/(x^2 -18x +72) + 4/(x-6) factor the first denominator. Get a common denominator. Combine terms. I will be happy to critique your work. ok hers goes 4x/(x-6)(x-12) + 4/(x-6)= 4x + 4/(x-6)(x -12) or am …
5. ### math/algebra

20 Divide: x^2 -49y^2/6x^2+42y divided by (x^2-7xy) = factor the first term. Multiply the first term by the inverse of the second.Combine terms. I will be happy to critique your work. (x-3)(x+5)/2(2x^2) * 2x-10 /x^2 - 25 = x-3/2x^2 …
6. ### Algebra

combine like terms -9x - 13x + 7 easy problem My professor says I have an error in combine "x" terms -22x + 7 help!
7. ### Math!

1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4?
8. ### Alg1

Given 4√50 - 2√8 observe that √50 =√25*2 and √8=√4*2 and that 25 and 4 are perfect squares, so I simplify the expression to 100√2 - 8√2 I can then combine these terms to get 92√2 …
9. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17
10. ### math

could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

More Similar Questions